The Effect of Creatine Supplement on The Kidney Function of Dragon Boat Athletes - Pitriani, Pipit; Ray, Hamidie Ronald RayDaniel; Darajat, Jajat (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2020)
The consumption of creatine supplement among amateur and professional athletes is increasing. The purpose of this study was to determine the effect of creatine supplementation on the kidney function of dragon boat athletes. 12 dragon boat athletes were divided into 2 groups, including one group that consumed creatine supplement and one group without creatine intake (placebo). Creatine supplement was given at a loading dose of 20gr/day. The frequency of creatine supplement intake was 3-4x a day. In the second week, the dose was reduced into 15 gr/day. Creatine supplements were consumed for 5 weeks. Blood urea and creatinine were taken from the median cubital vein of the arm by using a 3cc syringe. The results showed that creatine supplementation had a significant effect in increasing the level of blood urea and creatinine. Although there were increases in urea and creatinine levels in the blood, the amount was still within normal limits. Therefore, it should be anticipated by taking a sufficient water intake.Â AbstrakKonsumsi kreatin suplemen di kalangan atlet amatir dan profesional semakin meningkat. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh suplemen kreatin terhadap fungsi ginjal atlet dragon boat. 12 orang atlet dragon boat dibagi menjadi 2 kelompok, satu kelompok yang mengkonsumsi kreatin dan satu kelompok tanpa asupan kreatin (placebo). Suplemen kreatin diberikan dengan dosis loading 20gr/hari, frekuensi pemberian 3-4x sehari. Pada minggu kedua dosis diturunkan menjadi 15 gr/hari. Suplemen kreatin dikonsumsi selama 5 minggu. Kadar ureum dan kreatinin darah diambil dari vena median cubital lengan dengan menggunakan spuit 3cc. Hasil penelitian didapatkan pemberian suplemen kreatin berpengaruh signifikan meningkatkan kadar ureum dan kreatinin dalam darah. Walau terdapat peningkatan kadar ureum dan kreatinin dalam darah namun jumlahnya masih dalam batas normal, sehingga perlu diantisipasi dengan asupan cairan yang memadai.